PERSONAL CHALLENGES FACED BY FRONTLINE NURSE MANAGERS DURING THE COVID-19 PANDEMIC AT KAWEMPE NATIONAL REFERRAL HOSPITAL, KAMPALA DISTRICT. A CROSS-SECTIONAL STUDY. - Likico, Emily; Dr. Elisha Birungi (Student's Journal of Health Research Africa, 2025)
Background. Since early 2020, healthcare systems have been challenged worldwide due to the COVID-19 pandemic, and multiple challenges, such as rapid spread and limited treatment options for a formerly unknown disease, the number of contagious patients, and the prolonged duration of the pandemic, posed a significant burden on healthcare systems. This study examined Personal challenges faced by frontline nurse managers during the COVID-19 pandemic at Kawempe National Referral Hospital, Kampala District. Methodology. A descriptive cross-sectional study design and quantitative data collection method was used, 30 respondents were selected using convenience sampling procedure. Data was collected using questionnaires. Data was analyzed using excel data base and the results were presented inform of figures and tables. Results. 18 (60%) of the respondents were in the age range of 26 – 35 years, and 21 (70%) of the respondents were female. 25 (83.3%) of the respondents reported increased levels of stress, 21 (70%) reported increased anxiety and depression, 30 (100%) reported moral distress due to being unable to provide patients with the care they needed, 20 (66.7%) reported limited communication with patients, their families, and other health care professionals due to infection control measures, 18 (60%) reported failure to provide appropriate and adequate support to patients, 18 (60%) reported failure to make patient-centered decisions during provision of care and 30 (100%) reported burnout. Conclusion. Respondents reported various personal challenges faced by frontline Nurse managers during the COVID-19 pandemic, such as increased levels of stress, increased anxiety and depression, and moral distress due to being unable to provide patients with the care they needed. Recommendations There is a need to employ adequate numbers of staff to reduce workload and ensure that respondents can provide patient-centered care and effective service provision.